Provider–patient communication about prescription drug abuse: A qualitative analysis of the perspective of prescribers. Issue 1 (2nd January 2020) - Mathis, Stephanie M.; Hagaman, Angela; Hagemeier, Nicholas; Baker, Katie; Pack, Robert P.
Abstract: Background: Provider–patient communication underpins many initiatives aimed at reducing the public health burden associated with prescription drug abuse in the United States. The purpose of this qualitative analysis was to examine the characteristics of provider–patient communication about prescription drug abuse from the perspective of prescribers. Methods: From 2014 to 2015, 10 semi-structured interviews were conducted with a purposive sample of prescribers from multiple professions and medical fields in Central and South Central Appalachia. The interviews were conducted using a guide informed by Social Cognitive Theory and community theory research, audio-recorded, and transcribed verbatim. Thematic analysis, facilitated by NVivo 10 software, was used to generate themes. Results: Prescribers described 3 primary communication patterns with patients related to prescription drug abuse—informative, counteractive, and supportive. Prescribers also reported multiple factors—personal (e.g., education, experiences, and feelings of tension) and environmental (e.g., relationship with a patient, clinical resources, and policies on controlled prescription drugs)—that affect provider–patient communication and, by association, delivery of patient care related to prescription drug abuse. Conclusions: The findings suggest that provider–patient communication about prescription drug abuse is multidimensional and dynamic, characterized by multiple communication patterns and contributory factors. They have implications for (1) research aimed at advancing theoretical understanding of prescriber prescription drug abuse communication behaviors with patients and (2) interventions aimed at strengthening prescriber prescription drug abuse communication behaviors with patients.